Molecular basis of coagulation factor V deficiency caused by the R1698W inter-domain mutation - Calzavarini, Sara; Villoutreix, Bruno O.; Lunghi, Barbara; Livaja, Ruzica; Bernardi, Francesco; Dahlbäck, Björn (Thrombosis and Haemostasis, 2013)
Coagulation factor V (FV) deficiency is characterised by variable bleeding phenotypes and heterogeneous mutations. To add new insights into the FV genotype-phenotype relationship, we characterised the R1698W change in the A3 domain, at the poorly investigated interface with the A2 domain. The FV R1698W mutation was responsible for a markedly reduced expression level (10% of FV-WT) and specific activity in thrombin generation (0.39). Interestingly, the FVa1698W showed rapid activity decay upon activation due to increased dissociation rate between the heavy and light chains. The importance of the size and charge of the residue at position 1698 was investigated by three additional recombinant mutants, FVR1698A, FVR1698Q, and FVR1698E. FVR1698A and FVR1698Q expression (30 and 45% of FV-WT), specific activity (both 0.57) and stability were all reduced. Noticeably, FVR1698E showed normal activity and stability despite poor expression (10% of FV-WT). These data indicate the essential role of R1698 for normal biosynthetic process and support local flexibility for positively or negatively charged residues to produce stable and functional A3-A2 domain interactions. Their experimental alteration produces a gradient of FV defects, which help to interpret the wide spectrum of phenotypes in FV-deficient patients.
Keywords: Factor V deficiency; factor V structure; A domains; genotype-phenotype relationship